Surgical Management of Unilateral Partial Limbal Stem Cell Deficiency: Conjunctival Autografts versus Simple Limbal Epithelial Transplantation - Shanbhag SS (Dove Medical Press, 2021)
Swapna S Shanbhag,1 Sanjay Chanda,1 Pragnya R Donthineni,1 Sayan Basu1– 3 1The Cornea Institute, L.V. Prasad Eye Institute, Hyderabad, Telangana, India; 2Center for Ocular Regeneration (CORE), L.V. Prasad Eye Institute, Hyderabad, Telangana, India; 3Brien Holden Eye Research Centre (BHERC), L.V. Prasad Eye Institute, Hyderabad, Telangana, IndiaCorrespondence: Sayan BasuBrien Holden Eye Research Centre (BHERC), L.V. Prasad Eye Institute, Road No. 2, Banjara Hills, Hyderabad, 500034, Telangana, IndiaTel +91 4030612555Fax +91 40-23548271Email sayanbasu@lvpei.orgPurpose: To evaluate the clinical outcomes of conjunctival autograft (CAG) versus simple limbal epithelial transplant (SLET) for management of unilateral partial limbal stem cell deficiency (LSCD).Methods: This retrospective, comparative, interventional case series evaluated 30 eyes of 30 patients with unilateral partial LSCD. After corneal pannus dissection, 17 patients underwent CAG where graft was harvested from the ipsilateral or contralateral eye, while 13 patients underwent SLET where limbal biopsy was harvested from the contralateral eye. The primary outcome measure was anatomical success in the form of restoration of a completely epithelised, stable, and avascular corneal surface at last follow-up.Results: Both groups were comparable in terms of age at time of surgery, preoperative best-corrected visual acuity, median duration since injury, number of clock hours of limbus involved, and number of previous surgeries performed. The most common etiology for LSCD was chemical burns in both groups. The median duration of post-operative follow-up was 5.6 months [interquartile range [(IQR): 3.6– 15.1] in the CAG group versus 6.2 months (IQR: 4.5– 12.2) in the SLET group (p=0.75)]. The anatomical success rates were 86.5 ± 8.9% in the CAG group and 28.3 ± 13.7% in the SLET group at final follow-up visit (p = 0.025). Most failures in both groups occurred within the first 8 months after surgery.Conclusion: For eyes with unilateral partial LSCD secondary to chemical burns, CAG is a safe and effective method for restoring the corneal epithelium. Limbal transplantation may not be necessary for the treatment of partial LSCD.Keywords: partial limbal stem cell deficiency, ocular chemical burn, simple limbal epithelial transplantation, conjunctival autograft, symblepharon